A efetividade da audiência pública como forma de controle da administração pública por meio da participação popular - Albuquerque, Alfredo Monteiro Lins de (2023)
This dissertation analyzes participatory democracy, presenting the public hearing as a mechanism for direct popular action, aiming at promoting the control of management acts of Public Administration by civil society. Initially, we seek to identify how Brazilian law deals with the evolution of the Rule of Law to Democratic Rule of Law, enshrining the democratic principle of popular participation, with the aim of expanding the direct involvement of society in decision-making, inspection of state activity, in accountability, that is, the satisfaction of the public interest. The goal is to demonstrate, through the holding of public hearing, the effectiveness of the administrator’s right to information on the projects intended by the Public Administration, to stand his position to interfere in the decisions made by the administrator with an impact on his sphere of competence, etc., with the aim of promoting the improvement of the legitimacy of provisions from the Public Power. The present study aims to clarify the importance of the public hearing as an institutional mechanism available to the Public Administration, designed to the realization of rights, not only individual but social, collective and diffuse, and, therefore, due to their essentiality aspects, subject to control, giving rise to a greater engagement of social participation in decisions regarding public policy on a practical level. Despite its non-binding character, the public hearing must be adopted as a legitimate tool for pursuing the collective interest, greatly influencing State action. Because it is characterized as merely opinionated, it induces the public manager to follow the guidance of the community, and in case he understands otherwise, the diligent motivation of the decision is imposed, with consideration of all discussions, contributions, and evidence. And, thus, developing channels aimed at the direct integration of individuals, acting individually or through representative entities, the Public Administration promotes the fundamental right of good administration observing the principles inscribed in art. 37, caput, of the 1988 Political Letter